Cardiac Risk and Disordered Eating: Decreased R Wave Amplitude in Women with Bulimia Nervosa and Women with Subclinical Binge/Purge Symptoms. (11th August 2016) - Green, Melinda; Rogers, Jennifer; Nguyen, Christine; Blasko, Katherine; Martin, Amanda; Hudson, Dominique; Fernandez‐Kong, Kristen; Kaza‐Amlak, Zauditu; Thimmesch, Brandon; Thorne, Tyler
Abstract: The purpose of the present study was threefold. First, we examined whether women with bulimia nervosa ( n = 12) and women with subthreshold binge/purge symptoms ( n = 20) showed decreased mean R wave amplitude, an indicator of cardiac risk, on electrocardiograph compared to asymptomatic women ( n = 20). Second, we examined whether this marker was pervasive across experimental paradigms, including before and after sympathetic challenge tasks. Third, we investigated behavioural predictors of this marker, including binge frequency and purge frequency assessed by subtype (dietary restriction, excessive exercise, self‐induced vomiting, and laxative abuse). Results of a 3 (ED symptom status) × 5 (experimental condition) mixed factorial ANCOVA (covariates: body mass index, age) indicated women with bulimia nervosa and women with subclinical binge/purge symptoms demonstrated significantly reduced mean R wave amplitude compared to asymptomatic women; this effect was pervasive across experimental conditions. Multiple regression analyses showed binge and purge behaviours, most notably laxative abuse as a purge method, predicted decreased R wave amplitude across all experimental conditions. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.